A Comparison of Ecological Memory of Lake Ice‐Off in Eight North‐Temperate Lakes. Issue 6 (4th June 2021) - Dugan, Hilary A.
Abstract: Ice‐off dates on lakes are some of the longest phenological records in the field of ecology, and some of the best evidence of long‐term climatic change. However, there has been little investigation as to whether the date of ice‐off on a lake impacts spring and summer ecosystem dynamics. Here, I analyzed 274 years of long‐term data from eight north temperate lakes in two climate zones to address whether lakes have ecological memory of ice‐off in the subsequent summer. Five metrics were investigated: epilimnion temperatures, hypolimnion temperatures, hypolimnetic oxygen drawdown, water clarity, and spring primary productivity. The response of the metrics to ice‐off date were variable across latitude and lake type. The northern set of lakes stratified quickly following ice‐off, and early ice‐off years resulted in significantly warmer hypolimnetic temperatures. Oxygen depletion in the hypolimnion was not impacted by ice‐off date, likely because in late ice‐off years the lakes did not fully mix. In the southern lakes, ice‐off date was not correlated to the onset of stratification, with the latter being a more dominant control on hypolimnetic temperature and oxygen. The implications of these findings is that as ice‐off date trends earlier in many parts of the world, the lakes that will likely experience the largest changes in spring and summer ecosystem properties are the lakes that currently have the longest duration of lake ice. In considering a future with warmer winters, these results provide a starting point for predicting how lake ecosystem properties will change with earlier ice‐off. Plain Language Summary: Lake ice is disappearing around the world. This slow loss of winter is a clear sign of climate change, but does the date of ice‐off impact spring and summer lake processes? Untangling a memory effect of ice‐off from other factors, such as spring and summer weather, requires decades of monitoring data. Here, 274 years of lake records from eight lakes in two climate zones were analyzed to investigate whether lakes have ecological memory of ice‐off. The response of lake temperature, oxygen concentrations, and water clarity to ice‐off date were variable across latitude and lake size and type. It was found that when lakes stratify immediately following ice‐off, bottom water conditions have ecological memory of the timing of ice‐off. However, in lakes with a short duration of lake ice, this memory effect fades. The implication of this finding is that as ice‐off date trends earlier in many parts of the world, the lakes that will likely experience the largest changes in spring and summer lake ecosystem properties are the lakes that currently have the longest duration of lake ice. Key Points: Ice‐off date has variable impacts on ecosystem properties across lake type and climatic zone Lakes with a short duration of ice have little ecological memory of ice‐off date When lakes stratify immediately following ice‐off, ice‐off date impacts summer ecosystem properties